2023
DOI: 10.1242/jeb.245191
|View full text |Cite
|
Sign up to set email alerts
|

The microbiome buffers tadpole hosts from heat stress: a hologenomic approach to understand host–microbe interactions under warming

Abstract: Phenotypic plasticity is an important strategy that animals employ to respond and adjust to changes in their environment. Plasticity may occur via changes in host gene expression or through functional changes in their microbiomes, which contribute substantially to host physiology. Specifically, the presence and function of host-associated microbes can impact how animals respond to heat stress. We previously demonstrated that “depleted” tadpoles, with artificially disrupted microbiomes, are less tolerant to hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 78 publications
0
7
0
Order By: Relevance
“…Such findings indicate that temperature-based restructuring of the gut microbiota selects for bacterial taxa and/or functions that improve survival under heat stress. For example, Fontaine and Kohl (2023) found that the gut microbiome of larval green frogs exposed to a 24 hr period of heat stress significantly upregulated genes associated with carbohydrate metabolism, transcription, and translation. Surprisingly, they did not find that the heat stress altered bacterial expression of heat shock proteins (HSPs) within the gut microbiota, which are commonly upregulated in response to thermally stressful environments to maintain protein structure integrity (Feder and Hofmann, 1999).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Such findings indicate that temperature-based restructuring of the gut microbiota selects for bacterial taxa and/or functions that improve survival under heat stress. For example, Fontaine and Kohl (2023) found that the gut microbiome of larval green frogs exposed to a 24 hr period of heat stress significantly upregulated genes associated with carbohydrate metabolism, transcription, and translation. Surprisingly, they did not find that the heat stress altered bacterial expression of heat shock proteins (HSPs) within the gut microbiota, which are commonly upregulated in response to thermally stressful environments to maintain protein structure integrity (Feder and Hofmann, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…In line with the predictions of Lozupone et al (2012) and concept of disturbance ecology (Christian et al, 2015), we propose that exposure to different environmental temperatures represents a disturbance to the gut microbiota that causes a shift in bacterial, diversity, composition, and transcriptomics. While a rapid temperature shift can drastically alter gut microbiota transcriptomics of ectothermic vertebrates (Fontaine and Kohl, 2023; Zhou et al, 2022), community-wide changes are likely more pronounced following prolonged exposure to new temperatures enabling a new community to become established. Longitudinal studies measuring gut microbiota diversity metrics exposed to different acclimation temperatures (Baldassarre et al, 2022) would be beneficial in addressing this prediction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that the capacity for plastic adaptive responses of animal hosts to environmental stress may be modulated by the interactions between intrinsic (physiology and biochemical changes of the host) and extrinsic (host’s microbiome structure and function) mechanisms (Fontaine and Kohl, 2022; Marangon et al, 2021; Muñoz et al, 2019; Walke et al, 2021). It is unclear, however, to what extent these mechanisms are functionally linked as part of the whole organism’s adaptive response to survive in an extreme environment such as the tropical intertidal rocky shore.…”
Section: Introductionmentioning
confidence: 99%
“…Environmental microbes serve as a source for the assembly of host-associated microbial communities ( Loudon et al, 2014 ; Smith et al, 2015 ; Knutie et al, 2017 ; Jani and Briggs, 2018 ; Prest et al, 2018 ; Callens et al, 2020 ; Singh et al, 2020 ; Téfit et al, 2023 ), which in turn have been repeatedly shown to affect host health and Darwinian fitness ( Shin et al, 2011 ; Fraune et al, 2015 ; Shreiner et al, 2015 ; Sison-Mangus et al, 2015 ; Knutie et al, 2017 ; Gould et al, 2018 ; Popkes and Valenzano, 2020 ; Weiland-Bräuer et al, 2020 ). Environmental microorganisms can also directly influence host physiology by affecting immune maturation early in life, with possible fitness consequences later ( Chen and Cadwell, 2022 ; Fallet et al, 2022 ; Walsh and Guillemin, 2022 ; Donald and Finlay, 2023 ; Fontaine and Kohl, 2023 ). Studies done on frogs, for instance, have shown that raising tadpoles in an environment with reduced microbial diversity (autoclaved lake water) disrupts their gut microbiota and affects subsequent resistance to parasitic nematode infections, likely through affecting immune maturation ( Knutie et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%